Maternal pre-pregnancy body mass index, gestational weight gain and breastfeeding outcomes: a cross-sectional analysis - Hayley Martin; Kelly Thevenet-Morrison; Ann Dozier (BMC, 2020)
Abstract Background It is well established that mothers with above-normal pre-pregnancy BMI are at increased risk of breastfeeding cessation; however, the impact of pregnancy weight-gain (PWG) is less well-defined. Excess PWG may alter the hormonal preparation of breast tissue for lactation, increase the risk of complications that negatively impact breastfeeding (e.g. Cesarean-section, gestational diabetes), and may make effective latch more difficult to achieve. Methods Our objective was to determine the impact of PWG and pre-pregnancy BMI on the risk of breastfeeding cessation utilizing the Institute of Medicine's 2009 recommendations. Cox proportional hazards models were utilized to estimate the risk of cessation of exclusive breastfeeding, and cessation of any breastfeeding among women who initiated exclusive and any breastfeeding, respectively, in a cross sectional sample of survey respondents from a New York county (N = 1207). PWG category was interacted with pre-pregnancy BMI (3 levels of pre-pregnancy BMI, 3 levels of PWG). Confounders of the relationship of interest were evaluated using directed acyclic graphs and bivariate analyses; variables not on the proposed causal pathway and associated with the exposure and outcome were included in multivariate models. Results: After adjustment, women of normal and obese pre-pregnancy BMI with greater-than-recommended PWG had 1.39 (1.03-1.86) and 1.48 (1.06-2.07) times the risk of any breastfeeding cessation within the first 3 months postpartum compared to women with normal pre-pregnancy BMI who gained within PWG recommendations. Overweight women with greater-than-recommended PWG were at increased risk of cessation, although not significantly (aHR [95% CI]: 1.29 [0.95-1.75]). No significant relationship was observed for exclusive breastfeeding cessation. Conclusions Pre-pregnancy BMI and PWG may be modifiable risk factors for early breastfeeding cessation. Understanding the mechanism behind this risk should be ascertained by additional studies aimed at understanding the physiological, social, logistical (positioning) and other issues that may lead to early breastfeeding cessation.